Analisis Penggunaan Microsoft Excel dalam Penyusunan Laporan Keuangan pada Sistem Akuntansi Digital - Nur Aliyah Rahma Saleh; Masyhuri Masyhuri (Journal of Economic and Business Advancement, 2026)
This study examines the use of Microsoft Excel in the preparation of financial statements within the context of digital accounting systems through a qualitative non-empirical approach based on library research. The findings indicate that Microsoft Excel remains a widely utilized tool due to its flexibility, accessibility, and adaptability in supporting structured financial recording and reporting processes. However, its role extends beyond operational functionality, serving as a transitional platform that facilitates digital accounting adoption, particularly for entities with limited technological capacity. Despite these advantages, limitations related to system integration, internal control, scalability, and automation constrain its effectiveness in more complex environments. This research contributes conceptually by positioning Excel not as a replacement for accounting software, but as a strategic component within sustainable digital transformation frameworks.